Ecological Corridors as Management Tools - Freitas, Leonardo Esteves de; Garay, Irene Ester Gonzales (Seven Editora, 2023)
Full Protection Areas are central components of Brazil's nature conservation policy. These areas are responsible for protecting large fragments of natural ecosystems, as well as indigenous Lands. However, it is legitimate to ask whether the preservation of these fragments by itself ensures the long-term conservation of biodiversity. After all, the fragmentation of ecosystems, and the consequent fragmentation of natural populations, can lead to an increase in the rates of species extinction. It is postulated that the conservation of natural communities depends on the protection of the remaining native ecosystems, and on the expansion of connection between these fragments, reducing isolation and enhancing a greater gene flow of wild populations.  This new approach takes the scale of the landscape into account, requiring the participation of society in the processes of conservation and sustainable use of biodiversity, which leads to the notion of Ecological Corridors or Biodiversity Corridors. The implementation of these Corridors was adopted to find biodiversity conservation strategies that include human dimensions, make the corridors a tool for territorial ordering with the goals of 1) strengthening protected areas, 2) conserving the set of remaining ecosystems and 3) increasing the permeability of the landscape to the flow of species. Along with that, only the development and consolidation of sustainable human activities in the Corridors can confirm such an approach. The various objectives of the Ecological Corridor Conservation Strategy are addressed in this paper. DOI:https://doi.org/10.56238/alookdevelopv1-075